2019
DOI: 10.1016/j.abrep.2019.100197
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and mood after a normal night of drinking: A naturalistic alcohol hangover study in a non-student sample

Abstract: Aims The alcohol hangover is typically investigated in student samples. However, alcohol hangovers are also reported by non-student drinkers, beyond the age and drinking behaviors of a student sample. The aim of this study was to investigate the effects of a normal night of alcohol consumption on next-day cognitive performance in a non-student sample. Methods Participants ( N = 45) were recruited from a public drinking setting and participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Alcohol hangover is an unpleasant state that is reached after an episode of heavy drinking and starts once breath and blood alcohol levels have returned to zero [1]. Aside from symptoms like headaches and gastrointestinal problems [1], a wide range of mild cognitive impairments have been reported, including attention, memory, task-switching, and psychomotor performance deficits [2,3,4,5,7,67,68]. Importantly, these domains are also known to be impaired during acute alcohol intoxication [11,17,38,69,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol hangover is an unpleasant state that is reached after an episode of heavy drinking and starts once breath and blood alcohol levels have returned to zero [1]. Aside from symptoms like headaches and gastrointestinal problems [1], a wide range of mild cognitive impairments have been reported, including attention, memory, task-switching, and psychomotor performance deficits [2,3,4,5,7,67,68]. Importantly, these domains are also known to be impaired during acute alcohol intoxication [11,17,38,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, cognitive functions that are impaired by acute intoxication might also be impaired during alcohol hangover. Yet, the reports on this are still somewhat inconsistent, with some studies finding comparable effects, while others fail to do so [6,11,20,38,67,71,72]. Given that alcohol has repeatedly been reported to impair controlled behaviour to a larger degree than automatic behaviour [21], we decided to focus on how alcohol hangover impairs controlled versus automatic response selection processes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have utilised tasks of interference control—another form of inhibition [ 32 , 33 , 34 , 35 , 36 ]—and one recent study investigated the effects of hangover on response inhibition [ 37 ]. Three naturalistic studies asked participants to complete the Eriksen Flanker and Stroop tasks, measuring different aspects of interference control, in two conditions: the morning after a night of naturalistic drinking (hangover), and again after no alcohol consumption (no-hangover) [ 33 , 34 ]. In one study, student participants who were experiencing a hangover exhibited greater impairments in interference control on both tasks compared to the no-hangover condition [ 33 ], whilst another found impairments on the Stroop task only [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, student participants who were experiencing a hangover exhibited greater impairments in interference control on both tasks compared to the no-hangover condition [ 33 ], whilst another found impairments on the Stroop task only [ 32 ]. In contrast, a naturalistic study that recruited participants from the general population showed no hangover effects on interference control on either task [ 34 ]. One study that experimentally induced hangover also found no evidence of hangover-related effects on interference control using the Eriksen Flanker task [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, hungover participants did not seem to alter their application of goal-directed and/or habitual learning strategies 28 . Yet still, alcohol hangover has been shown to impair cognitive control functions 29 33 , which could promote a relative advantage of response automatization as well as poor behavioral choices beyond acute intoxication, like the habitual continuation of drinking.…”
Section: Introductionmentioning
confidence: 99%